Commercial vegetable production under protected structures in saline environments: A promising strategy for livelihood security - Meena, R. L.; Meena, B. L.; Chandra, Priyanka; Sanwal, S. K.; Narjary, Bhaskar (Indian Farming, 2025)
Salinity and water scarcity are major constraints in arid and semi-arid regions of India, where a large share of groundwater is saline. Protected cultivation through polyhouses, shade nets and tunnels provides a viable option for vegetable production under such environments. These structures improve microclimate, enhance water and nutrient use efficiency and enable the safe utilization ofsaline water. Crops like tomato, capsicum and chilli perform well under drip fertigation and raisedbed systems in polyhouses. Technologies such as grafting, mulching, soilless media and saline water blending reduce salt stress and improve yield and quality. With higher profitability, employment generation and government support, protected cultivation offers a promising strategy for livelihood and nutritional security.